Rolling Massage Punggung Berpengaruh Terhadap Pengeluaran ASI Pada Ibu Menyusui - Sari, Niki Winda; Maryati, Syiska Atik; Susilawati, Susilawati (Malang Journal of Midwifery (MAJORY), 2020)
The puerperium period is the initial period of breastfeeding and is a determinant of the success of exclusive breastfeeding, but there are still many formula feedings because breast milk does not come out immediately at the first puerperium. Rolling back massage is a method of overcoming barriers to breastfeeding at the beginning of birth, which is to speed up the timing of breastfeeding. The study aimed to analyze the effect of back massage on the timing of breastfeeding for breastfeeding mothers. This type of pre-experimental research used intact-group comparison design, a population of 30 nursing mothers, using purposive sampling technique according to inclusion criteria, research instruments using observation sheets and SOPs. Divided into 2 groups, the observation and treatment groups, the treatment group who received back massage for 2-3 minutes twice a day. The results showed that the group that was given the back massage technique had a mean value of 11 while the group that was not given a back massage had a mean value of 19. This means that those who are given a rolling back massage when breastfeeding is faster than those who are not given a rolling back massage. Analysis of the data using the Mann Whitney test obtained a p-value of 0.028 which indicates that there is an effect of rolling back massage on the timing of breastfeeding. Midwives can provide a back massage technique for mothers who do not immediately come out of breast milk at the beginning of birth, so that the time to release breast milk is faster. Keywords: Back Rolling Massage, Mother's Milk, Delivery Time.